PENGARUH LITERASI KEUANGAN, INKLUSI KEUANGAN DAN FINANCIAL TECHNOLOGY TERHADAP PENGELOLAAN KEUANGAN UMKM KECAMATAN MOJOROTO KOTA KEDIRI - Azziza Ainun Nabilla; Puji Astuti; Diah Nurdiwaty (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to examine the influence of financial literacy, financial inclusion, and financial technology on the financial management of Micro, Small, and Medium Enterprises (MSMEs) in Mojoroto District, Kediri City. Effective financial management is essential for business sustainability; however, many MSME owners still face challenges in transaction recording, financial reporting, access to financial services, and the utilization of financial technology. This study employed a quantitative approach by collecting data through questionnaires distributed to MSME owners in Mojoroto District, Kediri City. The sample was selected using purposive sampling. The collected data were analyzed using multiple linear regression with SPSS software, supported by classical assumption tests, the coefficient of determination test, t-test, and F-test. The findings indicate that financial literacy, financial inclusion, and financial technology have a positive and significant influence on MSME financial management. These variables improve entrepreneurs' ability to manage financial resources, determine funding sources, manage financial risks, and plan future finances. Simultaneously, the three variables significantly contribute to improving the financial management performance of MSMEs. The study concludes that financial literacy, financial inclusion, and financial technology play a vital role in enhancing the financial management of MSMEs in Mojoroto District, Kediri City. Therefore, MSME owners are encouraged to improve their financial knowledge, optimize the use of formal financial services, and adopt financial technology to support effective financial management and business sustainability. Furthermore, the government and related institutions are expected to strengthen financial education programs and expand access to financial services and financial technology for MSMEs.